Non-hemorrhagic stroke following venomous snakebite: a case series - Devadas, Deepesh; C. N., Arunraj; A., Rajesh; Unnikrishnan,; Kumar, K. Shaji (International Journal of Research in Medical Sciences, 2025)
Snakebite envenomation remains a major public health issue in India, causing nearly 50,000 deaths annually. Hemotoxic venoms, particularly from viper bites, are well recognized for inducing coagulopathy and hemorrhagic complications; however, ischemic stroke following envenomation is a rare but important clinical entity. We present a case series of three patients who developed non-hemorrhagic ischemic strokes after Russell’s viper bites. All three had evidence of systemic envenomation with prolonged clotting times and received prompt treatment with anti-snake venom and fresh frozen plasma. Despite correction of coagulopathy, each developed focal neurological deficits. Neuroimaging revealed acute infarcts: right corona radiata infarct in Case 1, left middle cerebral artery territory infarction in Case 2, and multiple embolic infarcts in Case 3. All patients were managed with antiplatelet therapy, neuroprotective agents, and supportive care, with gradual neurological improvement. This series highlights that neurological deterioration after snakebite is not always attributable to neurotoxic effects or intracranial hemorrhage and should prompt evaluation for ischemic stroke. Early recognition, timely neuroimaging, and institution of stroke-specific management are critical in improving outcomes. Clinicians should maintain a high index of suspicion for ischemic stroke in snakebite victims presenting with new-onset focal deficits, as prompt intervention may prevent long-term morbidity and disability.